ChemInform Abstract: A Calcium Catalyzed Regioselective (5‐exo Dig) Tandem Process for the Synthesis of Fully Substituted Furans. Issue 31 (14th July 2016) - Yaragorla, Srinivasarao; Dada, Ravikrishna; Pareek, Abhishek; Singh, Garima
Abstract: Fused furans are prepared from alkynols and coumarins or cyclohexanediones via cascade reaction involving alkylation, 5‐exo dig cyclization, and isomerization.